Patternmaking fashion design - Armstrong, Helen Joseph (Dehra Dun : Pearson, 2014)
Patternmaking for Fashion Design is a comprehensive book for students of fashion designing. The book comprises of chapters on the different aspects of pattern making including dart manipulation, added fullness and contouring. In addition, the book consists of illustrations, detailed sketches and easy-to-understand explanations for patternmaking. This book is essential for fashion designers interested in learning how to create different and complex design patterns.
Keywords: Dart manipulation; Cowls; Swimwear